2020
DOI: 10.33448/rsd-v9i8.5170
|View full text |Cite
|
Sign up to set email alerts
|

A influência da dermatite atópica na vida das crianças

Abstract: Atopic dermatitis influences the psychological, neurological and social spheres, involving the patient, family and school because it generates symptoms that interfere negatively in the child's life. Objective: to identify the influence of atopic dermatitis on the child's life. Methodology: the searches were carried out in two bibliographic databases - PubMed and Scielo. Articles written in English and Portuguese, published from January 1985 to December 2016, were selected, related to: atopic dermatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
1
0
2
Order By: Relevance
“…In the past, there were only a few studies related to neurological consequences caused by atopic dermatitis and hyperactivity and attention deficit disorder were the first to be reported in children with atopic dermatitis (Zanandréa et al 2020). This fact corroborates the study by Yaghmaie et al (2013), who showed that a child with atopic dermatitis has a higher probability of developing attention deficit disorder, behavior problems, hyperactivity, depression and anxiety than children without atopic dermatitis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the past, there were only a few studies related to neurological consequences caused by atopic dermatitis and hyperactivity and attention deficit disorder were the first to be reported in children with atopic dermatitis (Zanandréa et al 2020). This fact corroborates the study by Yaghmaie et al (2013), who showed that a child with atopic dermatitis has a higher probability of developing attention deficit disorder, behavior problems, hyperactivity, depression and anxiety than children without atopic dermatitis.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, considered as one of the most prevalent childhood dermatological disease, atopic dermatitis in Brazil has a 5 to 10% incidence in children under their 12 years old, depending on the studied area (Pires et al 2017). In this context, it is noticed that the atopic dermatitis prevalence in Brazil may vary, both related to region and age group analyzed, with north and northeast regions having slightly higher cases number (Zanandréa et al 2020). Durovic et al (2019) in his study showed that the children's life quality ends up being affected in different ways according to their age group, and the most affected group, according to his studies, were children between 5 to 9 years old, followed by children aged 10 to 16 years old and subsequently those from 0 to 4 years old.…”
Section: Discussionmentioning
confidence: 97%
“…Ao discorrer sobre as comorbidades associadas a DA, Zanandréa et al, (2020), ressaltam que entre aqueles que sofrem de dermatite atópica, distúrbios mentais pronunciados são detectados em média em 20-35% dos casos. Na dermatite atópica grave, mais de 2/3 dos pacientes são dominados por patologia mental de registros psicopatológicos neuróticos e afetivostranstornos depressivos, ansiofóbicos e neurastênicos.…”
Section: Resultsunclassified
“…Logo, depreende-se que apesar dos sentimentos negativos e alterações no comportamento advindos da DA, os portadores para alcançarem um desfecho positivo no tratamento ressignificam-se como ativos. Zanandréa et al (2020), realizou uma pesquisa bibliográfica com abordagem sistemática sobre a influência da dermatite atópica na vida das crianças, observando uma interrelação entre a maior gravidade da doença e a prevalência aumentada de transtorno de déficit de atenção e hiperatividade (TDAH), transtornos de conduta, autismo, ansiedade e depressão. Além disso, têm-se também maiores índices de dependência emocional, medo, retração social, labilidade emocional e distúrbios do sono, consequentes principalmente ao prurido gerado pelas lesões.…”
Section: Manzoni Et Al 2012unclassified